Respon Pertumbuhan dan Hasil Tanaman Selada (Lactuca sativa L.) Terhadap Pemberian Dosis Pupuk Hijau dan Bokashi Kirinyuh pada Tanah Ultisol - Isnawati Isnawati; Zairin Zairin; Akhmad Gazali (Universitas Lambung Mangkurat, 2018)
This study aims to determine the response of growth and yield of lettuce (Lactuca sativa L.) to the dosage of green manure and bokashi kirinyuh on ultisol soil and to know the dose of green manure or bokashi kirinyuh which gives growth and yield of the highest lettuce plant. Performed At Greenhouse with Native Design. Factor A (type of fertilizer) is the type of green manure and bokashi while factor B (dose in the type of fertilizer) ie dose 125, 250 and 375 grams. So there are 6 treatments and repeated 4 times, so obtained 24 units of experiments and multiplied by 2 polybags, so there are 48 plants. In the observation of consumption harvest (40 days after planting) type of fertilizer affect the number of leaves and dry weight of the top of the plant. The dose in the fertilizer has a very significant effect on the wet weight of the upper part of the plant during the consumption harvest and the wet weight as the initial observation of the appearance of the flower. Bokashi with a dose of 375 grams yields the highest average against the wet weight of the upper part of the crop at the time of consumption harvest and at the onset of interest. The dose of 250 grams of bokashi is the best dose against the average wet weight of the top of the plant at the beginning of the flower